2022
DOI: 10.29309/tpmj/2022.29.08.6987
|View full text |Cite
|
Sign up to set email alerts
|

Parents influence on career choice of medical undergraduates.

Abstract: Objective: To determine the parents influence on career choice of undergraduates. Study Design: Cross-sectional study. Setting: Private Medical Colleges. Period: October 2021 to December 2021. Material & Methods: A sample size of 440 was taken. The inclusion criteria included medical undergraduate students and who gave consent. Non-probability convenient sampling technique was used. A questionnaire titled “PSESUCCQ (Parents Socio-Economic Status and Undergraduates Career Choice Questionnaire” was used. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Macro-level and micro-level factors that contribute to the parental socialization of individuals and have a subsequent influence on career decisions and success include parental SES, support, interpersonal relationships, parenting style, and role modelling. By reviewing what existing literature suggests regarding the degree to which parental socialization influences individual career choices and success, it may be suggested that parents provide practical assistance and scaffolding to their children regarding career decisions (Din et al, 2022). By providing sufficient support and aspiring towards a more successful future for their children, parents may influence the outcomes experienced by said child.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Macro-level and micro-level factors that contribute to the parental socialization of individuals and have a subsequent influence on career decisions and success include parental SES, support, interpersonal relationships, parenting style, and role modelling. By reviewing what existing literature suggests regarding the degree to which parental socialization influences individual career choices and success, it may be suggested that parents provide practical assistance and scaffolding to their children regarding career decisions (Din et al, 2022). By providing sufficient support and aspiring towards a more successful future for their children, parents may influence the outcomes experienced by said child.…”
Section: Discussionmentioning
confidence: 99%
“…When considering how parental influence may affect an individual's career choice and subsequent success, it is essential to consider the macro-level institutions that may function in this relationship, such as Socioeconomic Status (SES) and education. Research by Din et al (2022) suggests that parents' SES and education influence the career choice of medical students and graduates. The results showed that 50% claimed a role of parent's SES in the career choice of medicine.…”
Section: Macro-level Parental Influence: Socioeconomic Status and Edu...mentioning
confidence: 99%
See 2 more Smart Citations